2022
DOI: 10.3390/ijms232112770
|View full text |Cite
|
Sign up to set email alerts
|

iTRAQ Proteomics Identified the Potential Biomarkers of Coronary Artery Lesion in Kawasaki Disease and In Vitro Studies Demonstrated That S100A4 Treatment Made HCAECs More Susceptible to Neutrophil Infiltration

Abstract: Coronary artery lesions (CAL) are a major complication of Kawasaki disease (KD). The early prediction of CAL enables the medical personnel to apply adequate medical intervention. We collected the serum samples from the KD patients with CAL (n = 32) and those without CAL (n = 31), followed by a global screening with isobaric tagging for relative and absolute quantification (iTRAQ) technology and specific validation with an enzyme-linked immunosorbent assay (ELISA). iTRAQ identified 846 proteins in total in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…HCAECs are an important component of coronary arteries, and apoptosis of HCAECs is an essential factor leading to endothelial dysfunction in coronary arteries. Abnormally activated T cells and monocyte macrophages release a large number of cytokines and inflammatory mediators, which lead to endothelial cell dysfunction, impaired vascular function, lipid deposition, and proliferation of smooth muscle cells, ultimately leading to coronary artery lesions 25,26 . To further investigate the role of LL‐37, HCAECs were stimulated with human recombinant LL‐37, and as anticipated, LL‐37 significantly promoted apoptosis in HCAECs and significantly increased the expression levels of TLR4 and NLRP3.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…HCAECs are an important component of coronary arteries, and apoptosis of HCAECs is an essential factor leading to endothelial dysfunction in coronary arteries. Abnormally activated T cells and monocyte macrophages release a large number of cytokines and inflammatory mediators, which lead to endothelial cell dysfunction, impaired vascular function, lipid deposition, and proliferation of smooth muscle cells, ultimately leading to coronary artery lesions 25,26 . To further investigate the role of LL‐37, HCAECs were stimulated with human recombinant LL‐37, and as anticipated, LL‐37 significantly promoted apoptosis in HCAECs and significantly increased the expression levels of TLR4 and NLRP3.…”
Section: Discussionmentioning
confidence: 93%
“…Abnormally activated T cells and monocyte macrophages release a large number of cytokines and inflammatory mediators, which lead to endothelial cell dysfunction, impaired vascular function, lipid deposition, and proliferation of smooth muscle cells, ultimately leading to coronary artery lesions. 25 , 26 To further investigate the role of LL‐37, HCAECs were stimulated with human recombinant LL‐37, and as anticipated, LL‐37 significantly promoted apoptosis in HCAECs and significantly increased the expression levels of TLR4 and NLRP3. Previous studies reported that LL‐37 act on endothelial cells and contribute to the production of MCP‐1, ICAM‐1, affect the expression of cytokines IL‐1β, IL‐6, TNF‐a, and induce the production of IL‐17.…”
Section: Discussionmentioning
confidence: 95%
“…By applying identification parameters of a false determinate rate <0.01 for protein and peptide identification and requiring protein identification with at least one unique peptide, 688 proteins were assessed and quantified. Abundance quantification of these proteins was further analyzed by using Partek [25]. With parameters set at p-value < 0.05 and variation >1.25, 15 proteins exhibited differential abundances between the two groups.…”
Section: Resultsmentioning
confidence: 99%
“…Isobaric tag for relative and absolute quantitation (iTRAQ) constitutes a mass spectrometrybased proteomic quantification technique that employs the derivatization of primary amino groups within intact proteins, along with isobaric tags assigned to distinct peptide fragments [20][21][22][23][24][25]. The iTRAQ methodology affords the opportunity to simultaneously screen up to eight samples for differentially expressed proteins with exceptional sensitivity and specificity [26].…”
Section: Assessments Of Isobaric Tag For Relative and Absolute Quanti...mentioning
confidence: 99%